2006
DOI: 10.3109/2000-1967-042
|View full text |Cite
|
Sign up to set email alerts
|

A Morphometric Study on the Endometrium of Rat Uterus in Hypothyroid and Thyroxine Treated Hypothyroid Rats

Abstract: Hypothyroidism increases the rate of pregnancy loss. Other manifestations include menstrual disorder, and infertility. Serum levels of gonadotropins are low in hypothyroid patients. Though studies of uterine ultrastructure are well established as approaches to investigating the pathophysiology of infertility, they have scarcely been extended to the study of hypothyroid related infertility. The present study investigates the effect of hypothyroidism on the ultrastructure of uterine epithelium.Three groups of Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
1
19
0
1
Order By: Relevance
“…Kilic and co-workers reported no significant difference in the endometrial volume in HYPO-Rx compared to euthyroid patients (29). However, morphometric studies examining endometrial changes in rats showed a decrease in epithelial cell volume, height of the luminal epithelium, and absolute endometrial volume in hypothyroid rats (33,34). While these changes were less pronounced in levothyroxine-treated hypothyroid rats, hypothyroidism may cause structural changes in the epithelium that do not impact endometrial thickness but may affect implantation and clinical pregnancy rates.…”
Section: Discussionmentioning
confidence: 99%
“…Kilic and co-workers reported no significant difference in the endometrial volume in HYPO-Rx compared to euthyroid patients (29). However, morphometric studies examining endometrial changes in rats showed a decrease in epithelial cell volume, height of the luminal epithelium, and absolute endometrial volume in hypothyroid rats (33,34). While these changes were less pronounced in levothyroxine-treated hypothyroid rats, hypothyroidism may cause structural changes in the epithelium that do not impact endometrial thickness but may affect implantation and clinical pregnancy rates.…”
Section: Discussionmentioning
confidence: 99%
“…On treatment with PTU a drug which induces hypothyroidism and also on thyroidectomy in rats poorly developed uterus was seen [42]. Inuwa et al [50] reported that absolute epithelial cell volume as well the height of the luminal epithelium in hypothyroid rats decreased but endometrium thickness was significantly increased. Thus it might be concluded that thyroid hormones might be importantly concerned in the maintenance of the normal structure of uterine epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Chan and Ng [7] did not observe morphological changes in the uterus and fallopian tubes when hypothyroidism was induced in rats on postnatal day one, but they reported a decrease in the number of primordial, antral and Graafian follicles. However, it has been shown that hypothyroidism decreases the absolute epithelial cell volume and the height of the luminal epithelium in rat uterus as well as a decrease in muscle layer [13, 14]. They have suggested that THs might be importantly concerned in the maintenance of the normal structure of uterine epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that hypothyroidism in women causes irregular menstruation, frank infertility and difficulty in maintaining pregnancy [10], and hypothyroidism in rodents induces alterations in the estrous cycle and uterine morphology [13]. It has been reported that thyroidectomy causes a decrease in basal plasma levels of luteinizing hormone (LH) and follicle stimulating hormone (FSH) [8, 28].…”
Section: Introductionmentioning
confidence: 99%